Genetic analysis of scattered populations of the Indian eri silkworm, Samia cynthia ricini Donovan: differentiation of subpopulations - Pradeep,Appukuttannair R. (2011)
Deforestation and exploitation has led to the fragmentation of habitats and scattering of populations of the economically important eri silkworm, Samia cynthia ricini, in north-east India. Genetic analysis of 15 eri populations, using ISSR markers, showed 98% inter-population, and 23% to 58% intra-population polymorphism. Nei's genetic distance between populations increased significantly with altitude (R² = 0.71) and geographic distance (R² = 0.78). On the dendrogram, the lower and upper Assam populations were clustered separately, with intermediate grouping of those from Barpathar and Chuchuyimlang, consistent with geographical distribution. The Nei's gene diversity index was 0.350 in total populations and 0.121 in subpopulations. The genetic differentiation estimate (Gst) was 0.276 among scattered populations. Neutrality tests showed deviation of 118 loci from Hardy-Weinberg equilibrium. The number of loci that deviated from neutrality increased with altitude (R² = 0.63). Test of linkage disequilibrium showed greater contribution of variance among eri subpopulations to total variance. D'2IS exceeded D'2ST, showed significant contribution of random genetic drift to the increase in variance of disequilibrium in subpopulations. In the Lakhimpur population, the peripheral part was separated from the core by a genetic distance of 0.260. Patchy habitats promoted low genetic variability, high linkage disequilibrium and colonization by new subpopulations. Increased gene flow and habitat-area expansion are required to maintain higher genetic variability and conservation of the original S. c. ricini gene pool.